2017
DOI: 10.4012/dmj.2016-017
|View full text |Cite
|
Sign up to set email alerts
|

Fracture strength of CAD/CAM fabricated lithium disilicate and resin nano ceramic restorations used for endodontically treated teeth

Abstract: The purpose of the present study was to evaluate and compare the fracture strength and failure modes of endocrowns, zirconia post, and fiber post supported restorations and predict the clinical outcomes of six different prostheses used for endodontically treated teeth. Sixty (n=10) maxillary central incisors were restored with zirconia post/resin-nano-ceramic crown (ZrRNC), fiber post/resinnano-ceramic crown (FbRNC), zirconia post/lithium disilicate ceramic crown (ZrLDS), fiber post/lithium disilicate ceramic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 34 publications
(82 reference statements)
7
47
1
1
Order By: Relevance
“…The results of this in vitro study were in accordance with other studies, which showed that LDS had the highest fracture strength, especially under lateral loading. Gresnigt et al assessed the fracture resistance of molar endocrown restorations made of LDS (IPS e.max CAD; Ivoclar Vivadent AG) and RNC (Lava Ultimate; 3M ESPE) under axial and lateral loading; they recorded no significance difference between LDS and RNC under axial loading (2675 and 2428 N), respectively, But LDS recorded higher fracture resistance than RNC under lateral loading (1118 and 838 N), respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this in vitro study were in accordance with other studies, which showed that LDS had the highest fracture strength, especially under lateral loading. Gresnigt et al assessed the fracture resistance of molar endocrown restorations made of LDS (IPS e.max CAD; Ivoclar Vivadent AG) and RNC (Lava Ultimate; 3M ESPE) under axial and lateral loading; they recorded no significance difference between LDS and RNC under axial loading (2675 and 2428 N), respectively, But LDS recorded higher fracture resistance than RNC under lateral loading (1118 and 838 N), respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Endocrowns are indicated in cases of short crown, limited interocclusal space, and sufficient tooth substance especially enamel . They are also an alternative in cases of root complexes like calcification or curved shape …”
Section: Introductionmentioning
confidence: 99%
“…Our study was not in agreement with the study performed by Bankoglu Gungor et al [22] where they compared anterior endocrowns with same crown dimensions made from e.max and Lava Ultimate. They found no difference in fracture strength between the two materials.…”
Section: Endocrowncontrasting
confidence: 99%
“…To provide both an expedient coronal seal and definitive cuspal coverage restoration, the endocrown may provide an efficient treatment option. However, Biacchi and colleagues suggested endocrowns are best limited for molar restoration as bicuspids may present with unfavorable mastication force vectors, with Bindl et al further noting that bicuspids have less available bonding surface, greater height to width ratio, and smaller pulp chamber dimensions which all serve to intensify lever force vectors. These reports were recently reinforced by Guo and colleagues who reported that endocrowns displayed no advantage compared to conventional methods of restoring endodontically treated mandibular bicuspids.…”
Section: Discussionmentioning
confidence: 99%
“…For the restoration of endodontically treated teeth, CAD/CAM advocates emphasize the “endocrown” method, which consists of a merged crown and core unit adhesively bonded into the pulp chamber and the remaining tooth structure . The endocrown method is said to provide a more conservative option to traditional post and core restorative strategies while providing equitable results . Dejak and Młotkowski using an in silico finite element analysis reported that under simulated masticatory function the endocrown had lower dentin stress concentration than compared to traditional post and core methods.…”
Section: Introductionmentioning
confidence: 99%